Effects of vertical urban densification on indoor thermal comfort in free-running buildings: An analysis using the comfort time ratio index (CTR) - C. Caicedo-Moncayo; B. Beckers; J.A. Ojeda (Energy and Buildings, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Bent out of shape: The impact of deviating heart morphology on cardiac function in Atlantic salmon (Salmo salar L.) - Victoria Becker; Simona Kavaliauskiene; Daniel Morgenroth; Sudip Mahat; William E. Louch; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

Longitudinal Impacts of Forest Loss on Bartonella and Hemotropic Mycoplasma Dynamics in Vampire Bats Within a Fragmented Habitat - Lauren R. Lock; Kristin E. Dyer; Dmitriy V. Volokhov; Anni Yang; M. Brock Fenton; Nancy B. Simmons; Daniel J. Becker (Molecular Ecology, 2026)
Habitat fragmentation can negatively impact wildlife, including increasing infectious disease risk. We assessed spatiotemporal changes in pathogen dynamics in vampire bats ( Desmodus rotundus ) in response to habitat fragmentation using general linear mixed models to investigate the influence of site, year, and tree cover on Bartonella spp. and hemotropic Mycoplasma spp. (hemoplasmas) infection risk in bats in one large and one small forest fragment in Belize across seven years. While Bartonella infections were more likely in the final years of the study regardless of site, hemoplasma infection likelihood was not significantly different across years or sites. Bartonella infections were associated with increased forest loss in the large fragment only, whereas hemoplasma infections were not associated with forest loss. The effects of site, year, and forest loss on infection likelihood varied by pathogen genotype despite low model explanatory power. Neither site nor year was associated with bartonellae, but one genotype was positively associated with tree cover. Two hemoplasmas were influenced by year with differing trends: one genotype was negatively associated with tree loss across sites, while another was positively associated with forest loss at the small fragment only. Both pathogens were similarly influenced by bat demographics and showed instances of infection status and genotype switching. Our work suggests that the effects of habitat fragmentation on infection risk depend on both the pathogen and specific genotype, complicating expectations of how environmental change affects wildlife disease dynamics. Efforts to mitigate infectious disease impacts in fragmented systems should be tailored to specific pathogens of concern.

The influence of egg incubation and rearing temperature on heart morphology and function in farmed Atlantic salmon (Salmo salar) - Pia Skovholt Halvorsen; Sudip Mahat; Simen W. Larsen; Tuva M.G. Sørgaard; Victoria Becker; Daniel Morgenroth; Morten Strøm; Marit Stormoen; William E. Louch; Simona Kavaliauskiene; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

Long-term persistence of clonal resistant and multidrug resistant E. coli despite absence of antimicrobial use in weaned dairy heifer rearing systems in Switzerland - R.M. Schmid; E. Studer; A. Kapopoulou; B. Yilmaz; J. Becker (Veterinary Microbiology, 2026)

Kinetic observations of non-volatile phenolic compounds during storage and accelerated aging of white wine from Vitis vinifera L. cv. ‘Riesling’ - Friederike A. Schnitker; Katharina Becker; Christoph Schuessler; Claus Patz; Rainer Jung; Christof B. Steingass; Ralf Schweiggert (Food Chemistry, 2026)

Ecology of community reassembly: Movements and diets of megafauna during a decade of restoration in Mozambique - Matthew C. Hutchinson; Reena H. Walker; Joel O. Abraham; Justine A. Becker; Dominique D. Gonçalves; Ciara M. Nutter; Johan Pansu; Erin M. Phillips; Arjun B. Potter; Beto Soares Tenente; Marc E. Stalmans; Ryan A. Long; et al. (Ecology, 2026)
The last decade has brought a worldwide surge of interest in rewilding—the repopulation of large herbivores and carnivores—as a strategy for conserving species and reviving ecosystem functions. Rewilding initiatives, if closely monitored, can provide unique insights into the ecology of the world's largest animals at otherwise impossible spatial and temporal scales. Capitalizing on these opportunities, and developing a knowledge base to guide future restoration efforts, requires the collection and dissemination of long‐term data that document community reassembly. To date, such data are virtually nonexistent: most megafaunal restoration projects are nascent and/or have not been rigorously monitored. Since 2008, the Gorongosa Restoration Project, in Mozambique's Gorongosa National Park, has facilitated the recovery of megafauna populations that were severely depleted or extirpated during the country's civil war (1977–1992). For over a decade, we have monitored Gorongosa's large‐herbivore populations to understand how animal behavior and trophic interactions change as communities reassemble. Here, we present spatiotemporally explicit data sets on the movements and diets of large herbivores in Gorongosa between 2013 and 2025, along with annual rainfall data. This period encompassed extremes of climate (including some of the driest and wettest years on record) and the reintroduction, starting in 2018, of locally extinct apex predators and scavengers: African wild dog ( Lycaon pictus ), leopard ( Panthera pardus ), spotted hyena ( Crocuta crocuta ), and side‐striped jackal ( Lupulella adusta ). We used GPS telemetry to monitor 277 herbivores of seven species (listed below with number of individuals collared, median duration of tracking, and median number of locations per individual): Cape bushbuck ( Tragelaphus sylvaticus : 103 individuals; 280 days; 6646 fixes), nyala ( T. angasii : 37 individuals; 306 days; 6789 fixes), greater kudu ( T. strepsiceros : 80 individuals; 300 days; 17,365 fixes), common eland ( T. oryx : 10 individuals; 334 days; 15,783 fixes), waterbuck ( Kobus ellipsiprymnus : 22 individuals; 13 days; 2877 fixes), plains zebra ( Equus quagga : 7 individuals; 212 days; 1171 fixes), and African savanna elephant ( Loxodonta africana : 18 individuals; 706 days; 33,122 fixes). For 295 individuals that were immobilized during this work, we present morphological measurements (chest girth, body length, hind‐foot length, weight), reproductive status and nutritional condition (ultrasound measurements, palpation scores), and fate (mortality date and cause, if known). For diet analysis, we used DNA metabarcoding to identify and quantify the relative abundances of plant taxa in 3785 fecal samples from 27 mammal species belonging to 11 families and 7 orders. In all, we recorded 516 food‐plant taxa from at least 87 plant families and 39 orders. For Gorongosa's 15 most common large herbivores, the median sampling depth was 216 fecal samples per species (interquartile range 156–279); the overall median sampling depth was 92 samples per species (range 1–499). We include basic metadata collected in the field (e.g., date, time, GPS location, animal sex, and age) along with laboratory notes and information on plant taxonomic identification. These data are valuable not just as a window on one ecosystem's recovery from armed conflict, but also as a resource for macroecology, meta‐analysis, and synthetic studies of animal movement, diet, and the dynamics of community reassembly. The data are freely available for use and this paper should be cited whenever data are reused; see Data : Metadata : Class III.B.4 for additional details.

Functional and structural cardiac remodelling in farmed Atlantic salmon (Salmo salar) - Pia Skovholt Halvorsen; Sudip Mahat; Victoria Becker; Simona Kavaliauskiene; Tuva M.G. Sørgaard; Daniel Morgenroth; Morten Strøm; William E. Louch; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dynamic field testing of a 15-year-old friction pendulum base-isolated residential building - P.M. Calvi; A. Rapone; T.C. Becker; H. Sucuoglu; G. Gabbianelli; B. Chalarca; I. Lanese; G.J. O'Reilly; E. Rizzo-Parisi; F. Dacarro (Soil Dynamics and Earthquake Engineering, 2026)

Corrigendum to “Dynamic field testing of a 15-year-old friction pendulum base-isolated residential building” [Soil Dynam Earthq Eng 200 (2026) 109802] - P.M. Calvi; A. Rapone; T.C. Becker; H. Sucuoglu; G. Gabbianelli; B. Chalarca; I. Lanese; G.J. O'Reilly; E. Rizzo-Parisi; F. Dacarro (Soil Dynamics and Earthquake Engineering, 2025)

Chemical and toxicological evaluation of micropollutants degradation in tertiary municipal wastewater by H2O2/UVC - Gabrielly M. Santos; Lucas G. Costa; Eduardo O. Marson; Meliza A.S. Bessa; Raquel W. Becker; Carla F.G. Frois; Carla Sirtori; Adão S. Ferreira; Raquel M.F. Sousa; Waldomiro Borges Neto; Marcelo B. Santos; Solidônio R. Carvalho; et al. (Journal of Environmental Chemical Engineering, 2025)

Serous fat atrophy in forensic veterinary pathology of domestic mammals - Amanda Ø. Birk; Cecilie B. Becker; Henrik E. Jensen (Journal of Comparative Pathology, 2025)

Change Your Diet: How CO 2 , Plant Phenology and Genotype Alter Grapevine Quality and Affect Performance and Larval Transcriptome of an Insect Herbivore - Christine Becker; Christof B. Steingass; Heiko Vogel; Annette Reineke (Molecular Ecology, 2025)
Herbivorous insects need to cope with changing host plant biochemistry caused by abiotic and biotic impacts, to meet their dietary requirements. Larvae of the multivoltine European grapevine moth Lobesia botrana , one of the main insect pests in viticulture, feed on both flowers and berries. The nutritional value and defence compounds of these organs are changing with plant phenology and are affected by climate change which may accordingly alter plant–insect interactions. Here, we assessed the impacts of future elevated atmospheric CO 2 concentrations on the host plant quality of different grapevine organs and the larval performance and the transcriptome of L. botrana . Using the Geisenheim VineyardFACE facility, where ‘Riesling’ and ‘Cabernet Sauvignon’ were cultivated in the field under ambient or elevated (ca. + 20%) atmospheric CO 2 concentrations, we found that nutrient (amino acids and sugars) and defence compound (phenolic compounds) concentrations of inflorescences and ripening berries differed strongly due to plant phenology and less due to cultivar and CO 2 concentration. Assessing global gene expression after feeding on the respective organs, we found that larval transcriptomic plasticity largely mirrored the plant biochemical plasticity. Larval relative growth rate differed between treatments in a plant phenology‐dependent manner. Grape berries contained higher amino acid concentrations and altered phenolics profiles after larval feeding. In the near future, the grapevine– L. botrana interaction will probably change less because of elevated CO 2 concentrations than it does currently during one season. Changes associated with plant phenology, however, may be relevant for contemporary pest management.

Signatures of Polar Vortex Weakening in the MLTI: A Review - V. L. Harvey; D. Aggarwal; E. Becker; M. Bittner; B. Funke; L. Goncharenko; J. Jia; R. Lieberman; H.-L. Liu; V. Maliniemi; A. Marchaudon; H. Nesse; et al. (Surveys in Geophysics, 2025)
This paper is a collaborative effort that originated at the International Space Science Institute Workshop on “Physical links between Weather and Climate in Space and the Lower Atmosphere” held 22–26 January 2024. Many scientists attended that workshop and contributed their expertise related to polar vortex impacts on upper atmosphere variability. This paper summarizes well-known and newly reported signatures of polar vortex weakening on mesosphere–lower-thermosphere (MLT) temperature, winds, composition, planetary waves, gravity waves, tides, and ionospheric foF2. A variety of observational and modeling results are shown and are consistent with previously published variations in the dynamical and chemical state of the MLT and ionosphere during weak vortex events. We present Superposed Epoch Analysis (SEA) of upper atmosphere diagnostics and phenomena where day 0 is the onset of major SSWs. We also present SEAs where day 0 is the onset of stratopause warmings followed by elevated stratopause events. Our goal in performing two SEAs is to test the sensitivity of 10 hPa versus 1 hPa winds to predict upper atmosphere variability. Results suggest that zonal winds and the semidiurnal migrating solar tide (SW2) in the MLT are more sensitive to zonal wind reversals at 1 hPa rather than 10 hPa. Alternatively, the non-migrating DW2 tide in the equatorial upper mesosphere is best predicted by planetary wave-1 amplitudes in the winter high-latitude upper stratosphere rather than zonal wind reversals. A notable aspect of both SEAs is extremely large event-to-event variability in all diagnostics. Thus, conclusions drawn based on any one event are less robust than those based on many events.

Motivation and retrospective appraisal of psychedelic study participation: a qualitative study in healthy volunteers - Laura Ley; Matthias E. Liechti; Anna M. Becker; Isabelle Straumann; Aaron Klaiber; Friederike Holze; Severin B. Vogt; Denis Arikci; Yasmin Schmid (Psychopharmacology, 2025)
Rationale Little is known about motives of healthy volunteers to participate in psychedelic trials and how they appraise their study experience retrospectively. Objectives This paper explored reasons why healthy people register for psychedelic trials, factors that they considered to contribute to either positive or negative study experiences, and under which circumstances they would seek a psychedelic experience again. Methods This study used the data of 151 healthy volunteers who had ingested serotonergic psychedelics in one of six randomized, double-blind, placebo-controlled crossover trials at the same research site under similar conditions. The data were analyzed through qualitative content analysis. Results The predominant motivations to participate in a trial were interest in psychedelics and an appealing setting. Expectations involved personal development and the occurrence of typical psychedelic effects. Hopes included transformative processes. The setting factors that promoted a positive experience were music and access to nature, whereas the sterile hospital environment was considered bothersome. Most participants valued the trusting relationship with their investigator. The most commonly criticized investigator characteristics were a perceived lack of support and investigator-induced psychological discomfort. Most participants considered their expectations exceeded and would take the study substances again, preferably in a setting in nature with friends. Conclusions This paper identified four pivotal factors to be considered for psychedelic study experiences: (1) a secure interpersonal relationship, (2) an aesthetically pleasing environment, (3) access to nature, and (4) the use of music. This analysis reveals subjective views of volunteers in psychedelic Phase-I trials and may improve research standards.

Intestinal and peritoneal lesions in wounded umbilical outpouchings in pigs after transportation - B. Meyer Jørgensen; T. Birk Jensen; C. Brandt Becker; C. Kirkelun Flyger; M. Vive Christensen; A. Birch; H. Elvang Jensen (Journal of Comparative Pathology, 2025)

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Experimental Drought Suppresses Amphibian Pathogen Yet Intensifies Transmission and Disrupts Protective Skin Microbiome - Shannon Buttimer; Daniel Medina; Renato A. Martins; Ana Gabrielle Morais da Silva; Wesley J. Neely; Célio F. B. Haddad; Graziella V. DiRenzo; Alessandro Catenazzi; Rayna C. Bell; C. Guilherme Becker (Global Change Biology, 2025)
Shifting precipitation regimes driven by global climate change can alter vertebrate behavior and host‐symbiont relationships, potentially compromising host resistance to pathogen invasion. In Brazil's Atlantic Forest, a biodiversity hotspot, prior research identified drought as a key factor disrupting the skin microbiome, contributing to a die‐off of pumpkin toadlets due to the invasive waterborne fungal pathogen Batrachochytrium dendrobatidis (Bd). However, observational studies cannot disentangle the direct effect of moisture on Bd growth from increased amphibian activity during wet breeding seasons. Using field enclosures, we experimentally tested the influence of drought conditions on host microhabitat use, Bd disease dynamics, and the composition and predicted Bd‐inhibitory function of cutaneous bacterial communities. Each enclosure housed ecologically realistic densities of Brachycephalus pitanga , a micro‐endemic pumpkin toadlet. We simulated a short‐term drought in half of the enclosures using translucent tarp coverings. To track individual toadlets, we identified their unique markings and collected skin swabs biweekly over 3 months. We then implemented molecular techniques to quantify Bd loads and characterize skin bacterial diversity and composition over time. Our findings indicate that while drought may reduce overall Bd loads on hosts, this effect is partially offset by an increase in the use of water‐filled areas of the enclosures and by a disruption of the protective host skin microbiome. This study provides valuable insights into the cascading impacts of climate change on animal behavior, host‐symbiont interactions, and disease dynamics.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Forensic evaluation of tail-bite wounds in pigs in Denmark - Christoffer K. Flyger; Cecilie B. Becker; Benjamin M. Jørgensen; Henrik E. Jensen (Journal of Comparative Pathology, 2025)

Unique per- and polyfluoroalkyl substances (PFAS) source suggested by a Lake Trout (Salvelinus namaycush) PFAS profile in a temperate lake - Eric Levanduski; Susan F. Cushman; Lisa B. Cleckner; Wayne Richter; Jesse C. Becker; Trevor Massey; Jacques Rinchard; N. Roxanna Razavi (Science of The Total Environment, 2025)

The role of seasonal migration in predicting amphibian population persistence across fragmented tropical landscapes: an individual-based model - Tamilie Carvalho; Nereyda Falconi; Thomas White; Luciano Alves dos Anjos; Luís O. M. Giasson; Maurício Humberto Vancine; Célio F. B. Haddad; Luís Felipe Toledo; C. Guilherme Becker (Biodiversity and Conservation, 2025)

Cost-effective alternatives to facilitate biomonitoring and bioassessment of neotropical streams - Francisco Valente-Neto; Renato B. Dala-Corte; Almir M. Cunico; André L.B. Magalhães; Bruno S. Godoy; Cecília G. Leal; Diego M.P. Castro; Diego R. Macedo; Dilermando P. Lima-Junior; Éder A. Gubiani; Fabio de O. Roque; Fabrício B. Teresa; et al. (Science of The Total Environment, 2025)

Environmental contaminants assessment for frequently harvested migratory waterfowl in the Northeast Atlantic flyway - David B. Dayan; Brenda J. Hanley; Joshua Stiller; Wayne Richter; Ian D. Gregg; Nate R. Huck; Min T. Huang; Theodore C. Nichols; Henry M. Spliethoff; Jesse C. Becker; Lisa A. Murphy; Krysten L. Schuler (Science of The Total Environment, 2025)

Trans‐Specific Polymorphisms Between Cryptic Daphnia Species Affect Fitness and Behavior - Connor S. Murray; Madison Karram; David J. Bass; Madison Doceti; Dörthe Becker; Joaquin C. B. Nunez; Aakrosh Ratan; Alan O. Bergland (Molecular Ecology, 2025)
Shared polymorphisms, loci with identical alleles across species, are of unique interest in evolutionary biology as they may represent cases of selection maintaining ancient genetic variation post‐speciation, or contemporary selection promoting convergent evolution. In this study, we investigate the abundance of shared polymorphism between two members of the Daphnia pulex species complex. We test whether the presence of shared mutations is consistent with the action of balancing selection or alternative hypotheses such as hybridization, incomplete lineage sorting or convergent evolution. We analyzed over 2,000 genomes from six taxa in the D. pulex species group and examined the prevalence and distribution of shared alleles between the focal species pair, North American and European D. pulex . We show that North American and European D. pulex diverged over 10 million years ago, yet retained tens of thousands of shared polymorphisms. We suggest that the number of shared polymorphisms between North American and European D. pulex cannot be fully explained by hybridization or incomplete lineage sorting alone. We show that most shared polymorphisms could be the product of convergent evolution, that a limited number appear to be old trans‐specific polymorphisms, and that balancing selection is affecting convergent and ancient mutations alike. Finally, we provide evidence that a blue wavelength opsin gene with trans‐specific polymorphisms has functional effects on behavior and fitness in the wild.

ARSACS: Clinical Features, Pathophysiology and iPS-Derived Models - Ikhlass Haj Salem; Mathieu Blais; Valeria M. Zuluaga-Sánchez; Laurence Rouleau; Esther B. E. Becker; Nicolas Dupré (The Cerebellum, 2025)

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Echocardiography - a non-invasive alternative for assessing cardiac morphology and function in Atlantic salmon (Salmo salar L.) - Victoria Becker; Simona Kavaliauskiene; Erik Sandblom; Lucas A. Zena; Albin Gräns; William E. Louch; Ivar Sjaastad; Ida B. Johansen; Michael Frisk (Aquaculture, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Ecosystem Size Drives Patterns and Control Mechanisms of Mixotrophs Success Across Tropical Lakes: A Large-Scale Assessment of the Grand Écart Hypothesis - Mariana R. A. Costa; Leticia B. Quesado; Regina L. G. Nobre; Camila R. Cabral; Fabíola C. C. Dantas; Hugo Sarmento; André M. Amado; Vanessa Becker; Judit Padisák; Luciana S. Carneiro; Adriano Caliman (Ecosystems, 2024)
Mixotrophy, a physiological trait combining autotrophy and heterotrophy in one organism, significantly contributes to energy and matter transfer in aquatic ecosystems. However, understanding how environmental factors influence mixoplankton success across freshwater ecosystems has been uncertain. The grand écart hypothesis (GEH) posits that light and nutrient availability are key components of mixotrophs' niche, suggesting that ecosystem properties determine opposing gradients of light and nutrients, creating environmental filtering for mixotrophs. We hypothesized that ecosystem size, a property of lake ecosystems, mediates the prevalence of patterns and control mechanisms predicted by the GEH on mixoplankton relative biomass (MRB). Using data from 98 tropical lakes, we demonstrated that lake size mediates the inverse relationship between light and nutrient availability across ecosystems. Larger lakes have more light but low nutrients, while smaller lakes have more nutrients but greater shading. Light availability better explains MRB in small lakes, and nutrients better explain MRB in large lakes, with MRB values being higher in small lakes, with secondary influence from zooplankton herbivory. Our results validate the GEH as a significant framework for explaining patterns and control mechanisms of mixoplankton across tropical lakes. This study highlights the significance of lake size as an ecosystem property that generates opposing light and nutrient gradients, further emphasizing its importance for understanding mechanisms regulating freshwater phytoplankton community structure and functioning. Integrating lake size within the conceptual framework of the GEH could aid in explaining mixoplankton success over macroecological scales.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Decoupling the effect of hydraulic oil contamination on the flotation performance of UG2 PGE ore and its interaction with alteration minerals - T.A Tshinavhe; B. McFadzean; G. Nwaila; M. Becker (Minerals Engineering, 2024)

Electrochemical/computational analysis and the derivation of Pourbaix diagrams of redox-active structural and adsorbed species in uranyl peroxide clusters (U60) - Benjamin B. Gebarski; Udo Becker (Geochimica et Cosmochimica Acta, 2024)

Leaf Shelters Facilitate the Colonisation of Arthropods and Enhance Microbial Diversity on Plants - Danilo F. B. dos Santos; Jacob E. Herschberger; Bijay Subedi; Victoria M. Pocius; Wesley J. Neely; Sasha E. Greenspan; C. Guilherme Becker; Gustavo Q. Romero; Mônica F. Kersch‐Becker (Ecology Letters, 2024)
Shelter‐building insects are important ecosystem engineers, playing critical roles in structuring arthropod communities. Nonetheless, the influence of leaf shelters and arthropods on plant–associated microbiota remains largely unexplored. Arthropods that visit or inhabit plants can contribute to the leaf microbial community, resulting in significant changes in plant–microbe interactions. By artificially constructing leaf shelters, we provide evidence that shelter‐building insects influence not only the arthropod community structure but also impact the phyllosphere microbiota. Leaf shelters exhibited higher abundance and richness of arthropods, changing the associated arthropod community composition. These shelters also altered the composition and community structure of phyllosphere microbiota, promoting greater richness and diversity of bacteria at the phyllosphere. In leaf shelters, microbial diversity positively correlated with the richness and diversity of herbivores. These findings demonstrate the critical role of leaf shelters in structuring both arthropod and microbial communities through altered microhabitats and species interactions.

The role of pyruvate-induced enhancement of oxygen metabolism in extracellular purinergic signaling in the post-cardiac arrest rat model - Koichiro Shinozaki; Vanessa Wong; Tomoaki Aoki; Kei Hayashida; Ryosuke Takegawa; Yusuke Endo; Harshal Nandurkar; Betty Diamond; Simon C. Robson; Lance B. Becker (Purinergic Signalling, 2024)

Assessing policy preferences for preventing and managing wildfire in Greece - Kati Burton; Douglas Becker; Tasos Hovardas; Chloe B. Wardropper; Alexander Maas (Forest Policy and Economics, 2024)

Modeling coupled dynamics of an empirical predator-prey system to predict top predator recovery - Samantha N.M. Hamilton; M. Tim Tinker; Joseph Jackson; Joseph A. Tomoleoni; Michael C. Kenner; Julie L. Yee; Tom W. Bell; Max C.N. Castorani; Benjamin H. Becker; Brent B. Hughes (Biological Conservation, 2024)

Interactions between White Sharks (Carcharodon carcharias) and artificial reefs along the east-coast of Australia - Alistair Becker; Paul A. Butcher; Stephen Morris; Curtis Champion; Victor M. Peddemors; Michael B. Lowry; Matthew D. Taylor (Fisheries Research, 2024)

Ediacaran tectographs from the Itajaí Basin: A cautionary tale from the Precambrian - B. Becker Kerber; G.M.E.M. Prado; N.L. Archilha; L.V. Warren; M.G. Simões; L.M. Lino; F.R. Quiroz-Valle; L.D. Mouro; A. El Albani; A. Mazurier; P.S.G. Paim; F. Chemale; et al. (Precambrian Research, 2024)

Phytoplankton functional responses induced by extreme hydrological events in a tropical reservoir - Mariana R. A. Costa; Maria M. L. Cardoso; Géza B. Selmeczy; Judit Padisák; Vanessa Becker (Hydrobiologia, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Suitability of saltmarsh creeks as release locations for stocked Mulloway (Argyrosomus japonicus) - Alistair Becker; D. Stewart Fielder; Michael B. Lowry; Matthew D. Taylor (Estuarine, Coastal and Shelf Science, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Implications of habitat use and movement of stocked juvenile dusky flathead ( Platycephalus fuscus ) on stock enhancement release strategies - Alistair Becker; Hugh Pederson; Michael B. Lowry; D. Stewart Fielder; Matthew D. Taylor (Fisheries Management and Ecology, 2023)
Stocking of marine fish into coastal systems to augment natural recruitment is a growing practice adopted by fisheries managers around the world. Releasing fish directly into well‐resourced nursery grounds greatly increases survival and retention of stocked individuals but requires an understanding of juvenile habitat requirements. In eastern Australia, the dusky flathead ( Platycephalus fuscus ) is a highly regarded recreationally targeted species and the focus of an emerging stock enhancement programme, although little is known of their specific nursery habitat. Using acoustic telemetry, hatchery‐reared juveniles were monitored in Lake Macquarie to quantify habitat use and dispersal. Sandy areas adjacent to edges of seagrass beds were favoured, likely as foraging habitat. Within 5 weeks after release, fish were detected 5 km from the release site, but only at locations containing seagrass beds, so stocked fish likely disperse around estuaries to regions with suitable habitat. Future releases of dusky flathead should target areas containing patchy seagrass‐sand to optimise stocking outcomes. Beyond fisheries enhancement programmes, our findings highlight the importance of structured habitat, such as seagrass beds, for juvenile fish.

Classifying micropollutants by environmental risk in groundwater using screening analysis associated to a hybrid multicriteria method combining (Q)SAR tools, fuzzy AHP and ELECTRE - Raquel W. Becker; Débora S. Araújo; Letícia A. Jachstet; Alejandro Ruiz-Padillo; Bianca do Amaral; Jussara E. de Souza; Camila de V. Müller Athayde; Gustavo B. Athayde; Carla Sirtori (Science of The Total Environment, 2023)

Socio-oceanography: an opportunity to integrate marine social and natural sciences - Ekaterina Popova; Yevgeny Aksenov; Laurent O. Amoudry; Amani Becker; Lucy Bricheno; Jennifer M. Brown; Michael A. Clare; Alan Evans; Claire Evans; Sara E. Fowell; Svetlana Jevrejeva; Zoe Jacobs; et al. (Frontiers in Marine Science, 2023)
Marine natural sciences have been instrumental in helping society understand how ocean systems operate and the threats they face. However, there is a growing realisation that the societal challenges related to the marine environment can only be addressed through more effective integration with all aspects of social sciences. Nevertheless, to date, social sciences remain insufficiently integrated into marine research. Recognising historical weaknesses and drawing on the authors’ own experience of interdisciplinary research, albeit writing primarily from a natural marine science perspective, we propose a series of steps to promote integrated marine research inclusive of strong social science. We suggest that changing the perspectives and attitudes of natural scientists is key. The inherent interconnectivity between the ocean and society ensures that nearly everything we do in the marine natural sciences has the potential to influence and, perhaps address, ongoing and future societal challenges. Consequently, a key challenge for natural scientists is to recognise and communicate this in an accessible manner outside their own disciplines. To attempt to address these issues, we introduce the concept of “Socio-oceanography” which we define as an area of research that takes a “whole system” approach to the marine environment. It focuses on the challenges which require advancement of both natural and social science components, especially on those where the feedbacks between social and natural components are beginning to emerge. Here, we discuss its scope, challenges to its effective application and key steps to catalyse interdisciplinary approaches using this concept.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Genetic characterization of infectious spleen and kidney necrosis virus in Banggai cardinalfish Pterapogon kauderni identified from eight separate cases between 2000 and 2017 - Samantha A. Koda; Kuttichantran Subramaniam; Joseph M. Groff; Roy P. Yanong; Deborah B. Pouder; Matt Pedersen; Craig Pelton; Michael M. Garner; Nicholas B. D. Phelps; Anibal G. Armien; Michael W. Hyatt; Paul M. Hick; et al. (Journal of Fish Diseases, 2023)

Unusual occurrence of a mixed pod of false killer whales (Pseudorca crassidens) and common bottlenose dolphins (Tursiops truncatus) in the Beagle Channel (Argentina) - A. A. San Martín; M. N. Paso Viola; M. B. Tartaglia Gamarra; C. Ordoñez; N. Asplanato; M. Torres; A. Dellabianca; Y. A. Becker; L. Bergagna; N. A. Dellabianca; L. Riccialdelli (Polar Biology, 2023)

Lung regeneration post SARS-CoV-2 infection: is it all about pneumocytes type II? - F. Armando; L. Heydemann; G. Beythien; K. Becker; S. Stanelle-Bertram; B. Schaumburg; N. Mounogou Kouassi; S. Beck; M. Zickler; G. Gabriel; W. Baumgärtner; M. Ciurkiewicz (Journal of Comparative Pathology, 2023)

Host immune responses to enzootic and invasive pathogen lineages vary in magnitude, timing, and efficacy - Coby A. McDonald; C. Guilherme Becker; Carolina Lambertini; L. Felipe Toledo; Célio F. B. Haddad; Kelly R. Zamudio (Molecular Ecology, 2023)
Infectious diseases of wildlife continue to pose a threat to biodiversity worldwide, yet pathogens are far from uniform in virulence or host disease outcome. Within the same pathogen species, virulence can vary considerably depending on strain or lineage, in turn eliciting variable host responses. One pathogen that has caused extensive biodiversity loss is the amphibian‐killing fungus, Batrachochytrium dendrobatidis (Bd), which is comprised of a globally widespread hypervirulent lineage (Bd‐GPL), and multiple geographically restricted, enzootic lineages. Whereas host immunogenomic responses to Bd‐GPL have been characterized in a number of amphibian species, immunogenomic responses to geographically restricted, enzootic Bd lineages are less clear. To examine lineage‐specific host immune responses to Bd, we exposed a species of pumpkin toadlet, Brachycephalus pitanga , which is endemic to Brazil's Southern Atlantic Forest, to either the Bd‐GPL or the enzootic Bd‐Asia‐2/Brazil (hereafter Bd‐Brazil) lineage. Using temporal samples from early, mid, and late infection stages, we quantified functional immunogenomic responses over the course of infection using differential gene expression tests and coexpression network analyses. Host immune responses varied significantly with Bd lineage. Relative to controls, toadlet responses to Bd‐Brazil were weak at early infection (25 genes significantly differentially expressed), peaked by mid‐stage infection (414 genes), and were nearly fully resolved by late‐stage infection (nine genes). In contrast, responses to Bd‐GPL were magnified and delayed; toadlets significantly differentially expressed 111 genes early, 87 genes at mid‐stage infection, and 726 genes by late‐stage infection relative to controls. Given that infection intensity did not vary between mid‐ and late‐stage disease in either Bd‐Brazil or Bd‐GPL treatments, this suggests that pumpkin toadlets may be at least partially tolerant to the enzootic Bd‐Brazil lineage. In contrast, late‐stage immune activation against Bd‐GPL was consistent with immune dysregulation previously observed in other species. Our results demonstrate that both the timing of immune response and the particular immune pathways activated are specific to Bd lineage. Within regions where multiple Bd lineages co‐occur, and given continued global Bd movement, these differential host responses may influence not only individual disease outcome, but transmission dynamics at the population and community levels.

Investigating the reasons for the improvement in flotation grade and recovery of an altered PGE ore when using sodium silicate - A. Molifie; M. Becker; S. Geldenhuys; B. McFadzean (Minerals Engineering, 2023)

New perspectives in unresectable cholangiocarcinoma? Evaluation of chemosaturation with percutaneous hepatic perfusion as a palliative treatment option - Cornelia L. A. Dewald; Lena S. Becker; Timo C. Meine; Sabine K. Maschke; Frank K. Wacker; Anna Saborowski; Arndt Vogel; Jan B. Hinrichs (Clinical & Experimental Metastasis, 2023)
Cholangiocarcinoma (CCA) are the second most common primary liver tumors and carry a dismal prognosis. Chemosaturation with percutaneous hepatic perfusion (PHP) is a palliative, intra-arterial therapeutic approach that provides a high dose chemotherapy of the liver with reduced systemic exposure. Aim of this retrospective, monocentric study was to analyze PHP as a palliative treatment for unresectable CCA. Toxicity, adverse events and complications were classified using the Common Terminology Criteria for Adverse Events (CTCAE v5.0). Overall response rate (ORR) and disease control rate (DCR) were evaluated according to the Response Evaluation Criteria in Solid Tumors (RECIST1.1). Median overall survival (mOS), median progression-free survival (mPFS) and hepatic mPFS (mhPFS) were computed using Kaplan–Meier estimation. In total 17 patients were treated with 42 PHP between 10/2014 and 09/2020. No significant complications occurred during the interventions. mOS was 27.6 (interquartile range (IQR) 16.5–37) months from first diagnosis and 9.9 (IQR 3.8–21) months from first PHP. mPFS was 4 (IQR 2–7) and mhPFS was 4 (IQR 3–10) months. ORR was 25% and DCR 75%. Significant, but transient hematotoxicity was frequent with grade 3/4 thrombopenia after 50%, leukopenia after 26% and anaemia after 21% of the interventions. An increase of transaminases (AST increase after 21% and ALT increase after 14% of the PHP) developed more often than a deterioration of the liver synthesis capacity. Salvage treatment with PHP has the potential to prolong life in selected patients with unresectable, refractory cholangiocarcinoma. The interventional procedure is safe. Post-interventional toxicity is frequent but manageable.

Nicht-codierende RNA als Regulator der Neurogenese - Marius Schneider; Peter B. Becker (BIOspektrum, 2023)
Long, non-coding (Inc) RNAs emerge as crucial regulators of gene expression. Their ability to interact with DNA and protein mediates the recruitment of regulators to defined chromosomal loci. LncRNAs are particularly abundant in brain tissues where they are involved in cell specification. We described a novel lncRNA, RUS (RNA upstream to Slitrk3), which interacts with epigenetic regulators and contributes to shaping the gene expression program of neural precursor cells towards neurogenesis.

Mechanisms of individual variation in large herbivore diets: Roles of spatial heterogeneity and state‐dependent foraging - Reena H. Walker; Matthew C. Hutchinson; Arjun B. Potter; Justine A. Becker; Ryan A. Long; Robert M. Pringle (Ecology, 2023)
Many populations of consumers consist of relatively specialized individuals that eat only a subset of the foods consumed by the population at large. Although the ecological significance of individual‐level diet variation is recognized, such variation is difficult to document, and its underlying mechanisms are poorly understood. Optimal foraging theory provides a useful framework for predicting how individuals might select different diets, positing that animals balance the “opportunity cost” of stopping to eat an available food item against the cost of searching for something more nutritious; diet composition should be contingent on the distribution of food, and individual foragers should be more selective when they have greater energy reserves to invest in searching for high‐quality foods. We tested these predicted mechanisms of individual niche differentiation by quantifying environmental (resource heterogeneity) and organismal (nutritional condition) determinants of diet in a widespread browsing antelope (bushbuck, Tragelaphus sylvaticus ) in an African floodplain‐savanna ecosystem. We quantified individuals' realized dietary niches (taxonomic richness and composition) using DNA metabarcoding of fecal samples collected repeatedly from 15 GPS‐collared animals (range 6–14 samples per individual, median 12). Bushbuck diets were structured by spatial heterogeneity and constrained by individual condition. We observed significant individual‐level partitioning of food plants by bushbuck both within and between two adjacent habitat types (floodplain and woodland). Individuals with home ranges that were closer together and/or had similar vegetation structure (measured using LiDAR) ate more similar diets, supporting the prediction that heterogeneous resource distribution promotes individual differentiation. Individuals in good nutritional condition had significantly narrower diets (fewer plant taxa), searched their home ranges more intensively (intensity‐of‐use index), and had higher‐quality diets (percent digestible protein) than those in poor condition, supporting the prediction that animals with greater endogenous reserves have narrower realized niches because they can invest more time in searching for nutritious foods. Our results support predictions from optimal foraging theory about the energetic basis of individual‐level dietary variation and provide a potentially generalizable framework for understanding how individuals' realized niche width is governed by animal behavior and physiology in heterogeneous landscapes.

Hydroacoustic surveys reveal the distribution of mid-water fish around two artificial reef designs in temperate Australia - Alistair Becker; Michael B. Lowry; Ashley M. Fowler; Matthew D. Taylor (Fisheries Research, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Prospecting for a quinoline containing selenium for comorbidities depression and memory impairment induced by restriction stress in mice - Renata L. de Oliveira; Guilherme T. Voss; Karline da C. Rodrigues; Mikaela P. Pinz; Julia V. Biondi; Nicole P. Becker; Eduardo Blodorn; William B. Domingues; Allya Larroza; Vinícius F. Campos; Diego Alves; Ethel A. Wilhelm; et al. (Psychopharmacology, 2022)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Secondary rewards acquire enhanced incentive motivation via increasing anticipatory activity of the lateral orbitofrontal cortex - X. Yang; X. Liu; Y. Zeng; R. Wu; W. Zhao; F. Xin; S. Yao; K. M. Kendrick; R. P. Ebstein; B. Becker (Brain Structure and Function, 2021)

A Novel Framework to Predict Relative Habitat Selection in Aquatic Systems: Applying Machine Learning and Resource Selection Functions to Acoustic Telemetry Data From Multiple Shark Species - Lucas P. Griffin; Grace A. Casselberry; Kristen M. Hart; Adrian Jordaan; Sarah L. Becker; Ashleigh J. Novak; Bryan M. DeAngelis; Clayton G. Pollock; Ian Lundgren; Zandy Hillis-Starr; Andy J. Danylchuk; Gregory B. Skomal (Frontiers in Marine Science, 2021)
Resource selection functions (RSFs) have been widely applied to animal tracking data to examine relative habitat selection and to help guide management and conservation strategies. While readily used in terrestrial ecology, RSFs have yet to be extensively used within marine systems. As acoustic telemetry continues to be a pervasive approach within marine environments, incorporation of RSFs can provide new insights to help prioritize habitat protection and restoration to meet conservation goals. To overcome statistical hurdles and achieve high prediction accuracy, machine learning algorithms could be paired with RSFs to predict relative habitat selection for a species within and even outside the monitoring range of acoustic receiver arrays, making this a valuable tool for marine ecologists and resource managers. Here, we apply RSFs using machine learning to an acoustic telemetry dataset of four shark species to explore and predict species-specific habitat selection within a marine protected area. In addition, we also apply this RSF-machine learning approach to investigate predator-prey relationships by comparing and averaging tiger shark relative selection values with the relative selection values derived for eight potential prey-species. We provide methodological considerations along with a framework and flexible approach to apply RSFs with machine learning algorithms to acoustic telemetry data and suggest marine ecologists and resource managers consider adopting such tools to help guide both conservation and management strategies.

Structure, gating and interactions of the voltage-dependent anion channel - Eszter E. Najbauer; Stefan Becker; Karin Giller; Markus Zweckstetter; Adam Lange; Claudia Steinem; Bert L. de Groot; Christian Griesinger; Loren B. Andreas (European Biophysics Journal, 2021)
The voltage-dependent anion channel (VDAC) is one of the most highly abundant proteins found in the outer mitochondrial membrane, and was one of the earliest discovered. Here we review progress in understanding VDAC function with a focus on its structure, discussing various models proposed for voltage gating as well as potential drug targets to modulate the channel’s function. In addition, we explore the sensitivity of VDAC structure to variations in the membrane environment, comparing DMPC-only, DMPC with cholesterol, and near-native lipid compositions, and use magic-angle spinning NMR spectroscopy to locate cholesterol on the outside of the β-barrel. We find that the VDAC protein structure remains unchanged in different membrane compositions, including conditions with cholesterol.

Membrane-embedded TSPO: an NMR view - Gwladys Rivière; Garima Jaipuria; Loren B. Andreas; Andrei Leonov; Karin Giller; Stefan Becker; Markus Zweckstetter (European Biophysics Journal, 2021)
Translocator Protein (18 kDa) (TSPO) is a mitochondrial transmembrane protein commonly used as a biomarker for neuroinflammation and is also a potential therapeutic target in neurodegenerative diseases. Despite intensive research efforts, the function of TSPO is still largely enigmatic. Deciphering TSPO structure in the native lipid environment is essential to gain insight into its cellular activities and to design improved diagnostic and therapeutic ligands. Here, we discuss the influence of lipid composition on the structure of mammalian TSPO embedded into lipid bilayers on the basis of solid-state NMR experiments. We further highlight that cholesterol can influence both the tertiary and quaternary TSPO structure and also influence TSPO localization in mitochondria-associated endoplasmic reticulum membranes.

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

Effect of the foliar application of cyanobacterial hydrolysate (Arthrospira platensis) on the growth of Petunia x hybrida under salinity conditions - P. J. Bayona-Morcillo; B. M. Plaza; C. Gómez-Serrano; E. Rojas; S. Jiménez-Becker (Journal of Applied Phycology, 2020)

Percutaneous isolated hepatic perfusion (chemosaturation) with melphalan following right hemihepatectomy in patients with cholangiocarcinoma and metastatic uveal melanoma: peri- and post-interventional adverse events and therapy response compared to a matched group without prior liver surgery - C. L. A. Dewald; L. S. Becker; S. K. Maschke; T. C. Meine; T. A. Alten; M. M. Kirstein; A. Vogel; F. K. Wacker; B. C. Meyer; J. B. Hinrichs (Clinical & Experimental Metastasis, 2020)
To evaluate feasibility, frequency and severity of peri-procedural complications and post-procedural adverse events (AEs) in patients with advanced cholangiocarcinoma or liver metastasis of uveal melanoma and prior hemihepatectomy undergoing chemosaturation percutaneous hepatic perfusion (CS-PHP) and to analyze therapy response and overall survival compared to a matched group without prior surgery. CS-PHP performed between 10/2014 and 02/2018 were retrospectively assessed. To determine peri-procedural safety and post-procedural adverse events, hospital records and hematological, hepatic and biliary function were categorized using Common Terminology Criteria for Adverse Events (CTCAE) v5.0 (1–5; mild-death). Significance was tested using Wilcoxon signed-rank and Mann–Whitney U test. Kaplan–Meier estimation and log-rank test assessed survival. Overall 21 CS-PHP in seven patients (4/7 males; 52 ± 10 years) with hemihepatectomy (group hemihep ) and 22 CS-PHP in seven patients (3/7 males; 63 ± 12 years) without prior surgery (group noresection ) were included. No complications occurred during the CS-PHP procedures. Transient changes (CTCAE grade 1–2) of liver enzymes and blood cells followed all procedures. In comparison, group hemihep presented slightly more AEs grade 3–4 (e.g. thrombocytopenia in 57% (12/21) vs. 41% (9/22; p = 0.37)) 5–7 days after CS-PHP. These AEs were self-limiting or responsive to treatment (insignificant difference of pre-interventional to 21–45 days post-interventional values (p > 0.05)). One patient in group hemihep with high tumor burden died eight days following CS-PHP. No deaths occurred in group noresection . In comparison, overall survival after first diagnosis was insignificantly shorter in group noresection (44.7(32–56.1) months) than in group hemihep (48.3(34.6–72.8) months; p = 0.48). The severity of adverse events following CS-PHP in patients after hemihepatectomy was comparable to a matched group without prior liver surgery. Thus, the performance of CS-PHP is not substantially compromised by a prior hemihepatectomy.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Anchitheriinae (Perissodactyla, Equidae) from the early middle Miocene locality Gračanica (Bugojno Basin, Bosnia-Herzegovina) - Damien Becker; Jérémy Tissier; Davit Vasilyan; Ursula B. Göhlich (Palaeobiodiversity and Palaeoenvironments, 2020)

Assessing amphibian disease risk across tropical streams while accounting for imperfect pathogen detection - José Wagner Ribeiro; Tadeu Siqueira; Graziella V. DiRenzo; Carolina Lambertini; Mariana L. Lyra; Luís Felipe Toledo; Célio F. B. Haddad; C. Guilherme Becker (Oecologia, 2020)

Reactive navigation system based on H∞ control system and LiDAR readings on corn crops - A. E. B. Velasquez; V. A. H. Higuti; H. B. Guerrero; M. V. Gasparino; D. V. Magalhães; R. V. Aroca; M. Becker (Precision Agriculture, 2020)

Ecological and evolutionary drivers of haemoplasma infection and bacterial genotype sharing in a Neotropical bat community - Daniel J. Becker; Kelly A. Speer; Alexis M. Brown; M. Brock Fenton; Alex D. Washburne; Sonia Altizer; Daniel G. Streicker; Raina K. Plowright; Vladimir E. Chizhikov; Nancy B. Simmons; Dmitriy V. Volokhov (Molecular Ecology, 2020)
Most emerging pathogens can infect multiple species, underlining the importance of understanding the ecological and evolutionary factors that allow some hosts to harbour greater infection prevalence and share pathogens with other species. However, our understanding of pathogen jumps is based primarily around viruses, despite bacteria accounting for the greatest proportion of zoonoses. Because bacterial pathogens in bats (order Chiroptera) can have conservation and human health consequences, studies that examine the ecological and evolutionary drivers of bacterial prevalence and barriers to pathogen sharing are crucially needed. Here were studied haemotropic Mycoplasma spp. (i.e., haemoplasmas) across a species‐rich bat community in Belize over two years. Across 469 bats spanning 33 species, half of individuals and two‐thirds of species were haemoplasma positive. Infection prevalence was higher for males and for species with larger body mass and colony sizes. Haemoplasmas displayed high genetic diversity (21 novel genotypes) and strong host specificity. Evolutionary patterns supported codivergence of bats and bacterial genotypes alongside phylogenetically constrained host shifts. Bat species centrality to the network of shared haemoplasma genotypes was phylogenetically clustered and unrelated to prevalence, further suggesting rare—but detectable—bacterial sharing between species. Our study highlights the importance of using fine phylogenetic scales when assessing host specificity and suggests phylogenetic similarity may play a key role in host shifts not only for viruses but also for bacteria. Such work more broadly contributes to increasing efforts to understand cross‐species transmission and the epidemiological consequences of bacterial pathogens.

Comparative in vitro activity of bacteriophage endolysin HY-133 against Staphylococcus aureus attached to vascular graft surface - Evgeny A. Idelevich; Dennis Knaack; Nyityasmono Tri Nugroho; Georg Peters; Theodosios Bisdas; Sonja Molinaro; Giovanni B. Torsello; Karsten Becker; Monika Herten (Medical Microbiology and Immunology, 2020)

Analysis of a Protein Network Related to Copy Number Variations in Autism Spectrum Disorder - Jaqueline B. Schuch; Vanessa R. Paixão-Côrtes; Dânae Longo; Tatiana Roman; Rudimar dos S. Riesgo; Josiane Ranzan; Michele M. Becker; Mariluce Riegel; Lavinia Schuler-Faccini (Journal of Molecular Neuroscience, 2019)

Amphibian skin fungal communities vary across host species and do not correlate with infection by a pathogenic fungus - Daniel Medina; Myra C. Hughey; Jenifer B. Walke; Matthew H. Becker; Katherine Pontarelli; Shan Sun; Brian Badgley; Lisa K. Belden (Environmental Microbiology, 2019)
Summary Amphibian population declines caused by the fungus Batrachochytrium dendrobatidis (Bd) have prompted studies on the bacterial community that resides on amphibian skin. However, studies addressing the fungal portion of these symbiont communities have lagged behind. Using ITS1 amplicon sequencing, we examined the fungal portion of the skin microbiome of temperate and tropical amphibian species currently coexisting with Bd in nature. We assessed cooccurrence patterns between bacterial and fungal OTUs using a subset of samples for which bacterial 16S rRNA gene amplicon data were also available. We determined that fungal communities were dominated by members of the phyla Ascomycota and Basidiomycota, and also by Chytridiomycota in the most aquatic amphibian species. Alpha diversity of the fungal communities differed across host species, and fungal community structure differed across species and regions. However, we did not find a correlation between fungal diversity/community structure and Bd infection, though we did identify significant correlations between Bd and specific OTUs. Moreover, positive bacterial–fungal cooccurrences suggest that positive interactions between these organisms occur in the skin microbiome. Understanding the ecology of amphibian skin fungi, and their interactions with bacteria will complement our knowledge of the factors influencing community assembly and the overall function of these symbiont communities.

Beta diversity of stream fish communities along anthropogenic environmental gradients at multiple spatial scales - Renato B. Dala-Corte; Luciano F. Sgarbi; Fernando G. Becker; Adriano S. Melo (Environmental Monitoring and Assessment, 2019)

Antipredator response diminishes during periods of resource deficit for a large herbivore - B. A. Oates; J. A. Merkle; M. J. Kauffman; S. R. Dewey; M. D. Jimenez; J. M. Vartanian; S. A. Becker; J. R. Goheen (Ecology, 2019)
The starvation–predation hypothesis predicts that, during resource shortages, prey forego antipredator behavior and forage as much as possible to avoid starvation, even when risk of predation is high. We tested this hypothesis using GPS locations collected simultaneously from moose ( Alces alces ) and wolves ( Canis lupus ) in the Greater Yellowstone Ecosystem of North America. We assessed shifts in the speed, displacement, and habitat selection of moose 24 h following encounter with wolves (0–1,500 m distance). We examined whether the strength of antipredator behaviors would weaken as winter progressed and the nutritional condition of moose declined. Moose responded to wolf encounters by increasing their rate of movement in early winter, but only within 500 m distance. Importantly, these responses attenuated as winter progressed. Moose did not avoid their preferred foraging habitat (riparian areas) following encounters with wolves at any distance, and instead they more strongly selected riparian areas, especially in early winter. Our findings support theoretical predictions that resource deficits should dampen prey antipredator behavior, and suggest that nutritional condition of prey may buffer against run‐away risk effects in food webs involving large mammalian predators and prey.

Molecular detection of Mycoplasma ovis in an outbreak of hemolytic anemia in sheep from Veracruz, Mexico - J. M. Martínez-Hernández; G. G. Ballados-González; D. Fernández-Bandala; S. Martínez-Soto; V. Velázquez-Osorio; P. B. Martínez-Rodríguez; A. Cruz-Romero; E. Grostieta; Y. Lozano-Sardaneta; P. Colunga Salas; I. Becker; S. Sánchez-Montes (Tropical Animal Health and Production, 2019)

Nemertean taxonomy—Implementing changes in the higher ranks, dismissing Anopla and Enopla - Malin Strand; Jon Norenburg; José E. Alfaya; Fernando Ángel Fernández‐Álvarez; Håkan S Andersson; Sonia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Gregorio Bigatti; Irina Cherneva; Alexey Chernyshev; Brian M. Chung; et al. (Zoologica Scripta, 2019)

Effects of ketamine on brain function during response inhibition - M. Steffens; C. Neumann; A.-M. Kasparbauer; B. Becker; B. Weber; M. A. Mehta; R. Hurlemann; U. Ettinger (Psychopharmacology, 2018)

A domain-general brain network underlying emotional and cognitive interference processing: evidence from coordinate-based and functional connectivity meta-analyses - Taolin Chen; Benjamin Becker; Julia Camilleri; Li Wang; Shuqi Yu; Simon B. Eickhoff; Chunliang Feng (Brain Structure and Function, 2018)

Integrating real-time subsurface hydrologic monitoring with empirical rainfall thresholds to improve landslide early warning - Benjamin B. Mirus; Rachel E. Becker; Rex L. Baum; Joel B. Smith (Landslides, 2018)

Incorporating Social Diversity into Wildfire Management: Proposing “Pathways” for Fire Adaptation - Travis B Paveglio; Matthew S Carroll; Amanda M Stasiewicz; Daniel R Williams; Dennis R Becker (Forest Science, 2018)

The role of spider hunting mode on the strength of spider–plant mutualisms - Mônica F. Kersch-Becker; Bruno B. Grisolia; Maria J. O. Campos; Gustavo Q. Romero (Oecologia, 2018)

Investigating the Functional Role of an Artificial Reef Within an Estuarine Seascape: a Case Study of Yellowfin Bream (Acanthopagrus australis) - Matthew D. Taylor; Alistair Becker; Michael B. Lowry (Estuaries and Coasts, 2018)

A Simplified Method for Generating Purkinje Cells from Human-Induced Pluripotent Stem Cells - Lauren M. Watson; Maggie M. K. Wong; Jane Vowles; Sally A. Cowley; Esther B. E. Becker (The Cerebellum, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Managing the development of artificial reef systems: The need for quantitative goals - Alistair Becker; Matthew D. Taylor; Heath Folpp; Michael B. Lowry (Fish and Fisheries, 2018)
Fisheries enhancement initiatives are a potentially useful tool for managers to supplement traditional approaches. Habitat‐based enhancements often deploy artificial reefs with the aim to increase the available structure to augment local production, yet current assessment approaches make it difficult to assess whether these reefs achieve pre‐deployment goals. This makes it hard for managers to determine whether artificial reefs could improve their fishery outputs, potentially leading to missed opportunities and reduced production. We reviewed 270 research articles to determine whether existing monitoring studies identify whether artificial reefs meet their pre‐deployment goals, thereby providing some evidence of their suitability for certain fisheries. We found only 62% of these studies clearly articulated the original goals of the reef. Goals were qualitative, and most studies were conducted over insufficient time frames to allow for ecological communities to stabilize and mature. It is therefore difficult to determine the success or failure of many artificial reefs in addressing the management issues for which they were deployed. In the light of these findings, we think the setting of explicit quantitative goals (which may be biological, social or economic), and monitoring the performance of reefs against these goals, could stimulate the broader application of artificial reefs in fisheries management strategies. Such an approach has been successfully adopted in aquaculture‐based fisheries enhancement, and we explain how current evaluation methods such as harvest strategies can be easily adapted to quantitatively monitor artificial reef performance.

Analysis of Herbivore Stress- and Phytohormone-Mediated Urease Expression in Soybean (Glycine max) - Angela Menegassi; Roberta Da Silva e Silva; Celia R. Carlini; Axel Mithöfer; Arlete B. Becker-Ritt (Journal of Plant Growth Regulation, 2018)

Evidence for Association Between OXTR Gene and ASD Clinical Phenotypes - Lucas de Oliveira Pereira Ribeiro; Pedro Vargas-Pinilla; Djenifer B. Kappel; Danae Longo; Josiane Ranzan; Michele Michelin Becker; Rudimar dos Santos Riesgo; Lavinia Schuler-Faccini; Tatiana Roman; Jaqueline Bohrer Schuch (Journal of Molecular Neuroscience, 2018)

Comprehensive analysis of phospholipids in the brain, heart, kidney, and liver: brain phospholipids are least enriched with polyunsaturated fatty acids - Jaewoo Choi; Tai Yin; Koichiro Shinozaki; Joshua W. Lampe; Jan F. Stevens; Lance B. Becker; Junhwan Kim (Molecular and Cellular Biochemistry, 2018)

De novo FBXO11 mutations are associated with intellectual disability and behavioural anomalies - Daniel Fritzen; Alma Kuechler; Mona Grimmel; Jessica Becker; Sophia Peters; Marc Sturm; Hela Hundertmark; Axel Schmidt; Martina Kreiß; Tim M. Strom; Dagmar Wieczorek; Tobias B. Haack; et al. (Human Genetics, 2018)

Response of estuarine consumer communities following the stocking of a juvenile penaeid ( Penaeus plebejus ) over two consecutive years - A. Becker; M. B. Lowry; M. D. Taylor (Fisheries Management and Ecology, 2018)
Research programmes that monitor and evaluate the impact of stocking activities are essential to quantify effects of stocking and provide information for adaptive management of future releases. The consumer communities in two estuaries stocked with 5.8 million post‐larvae eastern king prawn Penaeus plebejus (Hess) were monitored, both before and after stocking, and relative to two similar reference estuaries. Following stocking, there was evidence of increases in the abundances of prawns within stocked estuaries. Communities in all four estuaries showed significant levels of variation over time as well as among the systems themselves. Changes in overall diversity were similarly observed. The presence or absence of vegetation and other seasonal effects were found to explain most of the observed variation in the community assemblage, while prawn stocking appeared to have a little detectable influence. While this study points to minimal impacts of prawn stocking on the consumer community at the densities used, research into potential shifts in resource use by competitors and the growth and survival of prawns is required to fully understand post‐release changes in stocked systems.

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

From Mice to Men: TRPC3 in Cerebellar Ataxia - Esther B. E. Becker (The Cerebellum, 2017)

The Geoid Slope Validation Survey 2014 and GRAV-D airborne gravity enhanced geoid comparison results in Iowa - Y. M. Wang; C. Becker; G. Mader; D. Martin; X. Li; T. Jiang; S. Breidenbach; C. Geoghegan; D. Winester; S. Guillaume; B. Bürki (Journal of Geodesy, 2017)

Dominance‐function relationships in the amphibian skin microbiome - Jenifer B. Walke; Matthew H. Becker; Myra C. Hughey; Meredith C. Swartwout; Roderick V. Jensen; Lisa K. Belden (Environmental Microbiology, 2017)
Summary Some amphibian skin bacteria inhibit growth of a fungal amphibian pathogen, Batrachochytrium dendrobatidis (Bd), but it is unclear how dominant these anti‐Bd bacteria are in skin communities. Using in vitro co‐culture challenge assays, we quantified Bd inhibition by bacterial isolates collected from the skin of four amphibian species: bullfrogs, Eastern newts, spring peepers and American toads. The 16S rRNA sequences for each isolate were matched to culture‐independent amplicon sequences from the same individuals to assess inhibitory function versus relative abundance. Dominant bacteria had higher Bd inhibition than rare bacteria in bullfrog and newt populations, in which Bd was prevalent (> 25%). Dominant and rare bacteria did not differ in Bd inhibition in spring peeper and toad populations, in which Bd was absent or at low prevalence (

Natural variation in life history strategy of Arabidopsis thaliana determines stress responses to drought and insects of different feeding guilds - Nelson H. Davila Olivas; Enric Frago; Manus P. M. Thoen; Karen J. Kloth; Frank F. M. Becker; Joop J. A. van Loon; Gerrit Gort; Joost J. B. Keurentjes; Joost van Heerwaarden; Marcel Dicke (Molecular Ecology, 2017)
Plants are sessile organisms and, consequently, are exposed to a plethora of stresses in their local habitat. As a result, different populations of a species are subject to different selection pressures leading to adaptation to local conditions and intraspecific divergence. The annual brassicaceous plant Arabidopsis thaliana is an attractive model for ecologists and evolutionary biologists due to the availability of a large collection of resequenced natural accessions. Accessions of A. thaliana display one of two different life cycle strategies: summer and winter annuals. We exposed a collection of 308 European Arabidopsis accessions, that have been genotyped for 250K SNPs, to a range of stresses: one abiotic stress (drought), four biotic stresses ( Pieris rapae caterpillars, Plutella xylostella caterpillars, Frankliniella occidentalis thrips and Myzus persicae aphids) and two combined stresses (drought plus P. rapae and Botrytis cinerea fungus plus P. rapae ). We identified heritable genetic variation for responses to the different stresses, estimated by narrow‐sense heritability. We found that accessions displaying different life cycle strategies differ in their response to stresses. Winter annuals are more resistant to drought, aphids and thrips and summer annuals are more resistant to P. rapae and P. xylostella caterpillars. Summer annuals are also more resistant to the combined stresses of drought plus P. rapae and infection by the fungus Botryris cinerea plus herbivory by P. rapae . Adaptation to drought displayed a longitudinal gradient. Finally, trade‐offs were recorded between the response to drought and responses to herbivory by caterpillars of the specialist herbivore P. rapae .

Habitat-Based Density Models for Three Cetacean Species off Southern California Illustrate Pronounced Seasonal Differences - Elizabeth A. Becker; Karin A. Forney; Bruce J. Thayre; Amanda J. Debich; Gregory S. Campbell; Katherine Whitaker; Annie B. Douglas; Anita Gilles; Ryan Hoopes; John A. Hildebrand (Frontiers in Marine Science, 2017)

Consensus Paper: Cerebellar Development - Ketty Leto; Marife Arancillo; Esther B. E. Becker; Annalisa Buffo; Chin Chiang; Baojin Ding; William B. Dobyns; Isabelle Dusart; Parthiv Haldipur; Mary E. Hatten; Mikio Hoshino; Alexandra L. Joyner; et al. (The Cerebellum, 2016)

Adaptive threat management framework: integrating people and turtles - Valéria R. F. da Silva; Sylvia F. Mitraud; Maria L. C. P. Ferraz; Eduardo H. S. M. Lima; Maria Thereza D. Melo; Armando J. B. Santos; Augusto César C. D. da Silva; Jaqueline C. de Castilhos; Jamyle A. F. Batista; Gustave G. Lopez; Frederico Tognin; João Carlos Thomé; et al. (Environment, Development and Sustainability, 2016)

An 8-year record of gas geochemistry and isotopic composition of methane during baseline sampling at a groundwater observation well in Alberta (Canada) - P. Humez; B. Mayer; M. Nightingale; J. Ing; V. Becker; Don Jones; Vien Lam (Hydrogeology Journal, 2016)

Phospholipid alterations in the brain and heart in a rat model of asphyxia-induced cardiac arrest and cardiopulmonary bypass resuscitation - Junhwan Kim; Joshua W. Lampe; Tai Yin; Koichiro Shinozaki; Lance B. Becker (Molecular and Cellular Biochemistry, 2015)

DNA barcoding and morphological identification of neotropical ichthyoplankton from the Upper Paraná and São Francisco - R. A. Becker; N. G. Sales; G. M. Santos; G. B. Santos; D. C. Carvalho (Journal of Fish Biology, 2015)
The identification of fish larvae from two neotropical hydrographic basins using traditional morphological taxonomy and DNA barcoding revealed no conflicting results between the morphological and barcode identification of larvae. A lower rate (25%) of correct morphological identification of eggs as belonging to migratory or non‐migratory species was achieved. Accurate identification of ichthyoplankton by DNA barcoding is an important tool for fish reproductive behaviour studies, correct estimation of biodiversity by detecting eggs from rare species, as well as defining environmental and management strategies for fish conservation in the neotropics.

The Potential Application of Mitochondrial Medicine in Toxicologic Poisoning - David H. Jang; Joshua W. Lampe; Lance B. Becker (Journal of Medical Toxicology, 2015)

Phylogenetic distribution of symbiotic bacteria from Panamanian amphibians that inhibit growth of the lethal fungal pathogen Batrachochytrium dendrobatidis - Matthew H. Becker; Jenifer B. Walke; Lindsey Murrill; Douglas C. Woodhams; Laura K. Reinert; Louise A. Rollins‐Smith; Elizabeth A. Burzynski; Thomas P. Umile; Kevin P. C. Minbiole; Lisa K. Belden (Molecular Ecology, 2015)
The introduction of next‐generation sequencing has allowed for greater understanding of community composition of symbiotic microbial communities. However, determining the function of individual members of these microbial communities still largely relies on culture‐based methods. Here, we present results on the phylogenetic distribution of a defensive functional trait of cultured symbiotic bacteria associated with amphibians. Amphibians are host to a diverse community of cutaneous bacteria and some of these bacteria protect their host from the lethal fungal pathogen Batrachochytrium dendrobatidis (Bd) by secreting antifungal metabolites. We cultured over 450 bacterial isolates from the skins of Panamanian amphibian species and tested their interactions with Bd using an in vitro challenge assay. For a subset of isolates, we also completed coculture experiments and found that culturing isolates with Bd had no effect on inhibitory properties of the bacteria, but it significantly decreased metabolite secretion. In challenge assays, approximately 75% of the bacterial isolates inhibited Bd to some extent and these inhibitory isolates were widely distributed among all bacterial phyla. Although there was no clear phylogenetic signal of inhibition, three genera, Stenotrophomonas, Aeromonas and Pseudomonas, had a high proportion of inhibitory isolates (100%, 77% and 73%, respectively). Overall, our results demonstrate that antifungal properties are phylogenetically widespread in symbiotic microbial communities of Panamanian amphibians and that some functional redundancy for fungal inhibition occurs in these communities. We hope that these findings contribute to the discovery and development of probiotics for amphibians that can mitigate the threat of chytridiomycosis.

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Hydrological variability of major French rivers over recent decades, assessed from gauging station and GRACE observations - L. Chevalier; B. Laignel; N. Massei; S. Munier; M. Becker; I. Turki; A. Coynel; A. Cazenave (Hydrological Sciences Journal, 2014)

The Moonwalker Mouse: New Insights into TRPC3 Function, Cerebellar Development, and Ataxia - Esther B. E. Becker (The Cerebellum, 2014)

Introduction - Martin B. Kalinowski; Andreas Becker (Pure and Applied Geophysics, 2014)

Long‐term endemism of two highly divergent lineages of the amphibian‐killing fungus in the A tlantic F orest of B razil - D. Rodriguez; C. G. Becker; N. C. Pupin; C. F. B. Haddad; K. R. Zamudio (Molecular Ecology, 2014)
The recent global spread of the amphibian‐killing fungus [ B atrachochytrium dendrobatidis ( Bd )] has been closely tied to anthropogenic activities; however, regional patterns of spread are not completely understood. Using historical samples, we can test whether B d was a spreading or endemic pathogen in a region within a particular time frame, because those two disease states provide different predictions for the regional demographic dynamics and population genetics of B d . Testing historical patterns of pathogen prevalence and population genetics under these predictions is key to understanding the evolution and origin of B d . Focusing on the A tlantic F orest ( AF ) of B razil, we used q PCR assays to determine the presence or absence of B d on 2799 preserved postmetamorphic anurans collected between 1894 and 2010 and used semi‐nested PCR s to determine the frequency of r RNA ITS 1 haplotypes from 52 samples. Our earliest date of detection was 1894. A mean prevalence of 23.9% over time and spatiotemporal patterns of B d clusters indicate that B d has been enzootic in the B razilian AF with no evidence of regional spread within the last 116 years. ITS 1 haplotypes confirm the long‐term presence of two divergent strains of B d ( B d GPL and B d‐Brazil ) and three spatiotemporally broad genetic demes within B d GPL , indicating that B d was not introduced into southeast B razil by the bullfrog trade. Our data show that the evolutionary history and pathogen dynamics of B d in B razil is better explained by the endemic pathogen hypothesis.

A System-based Paradigm of Drought Analysis for Operational Management - G. Tsakiris; I. Nalbantis; H. Vangelis; B. Verbeiren; M. Huysmans; B. Tychon; I. Jacquemin; F. Canters; S. Vanderhaegen; G. Engelen; L. Poelmans; P. De Becker; et al. (Water Resources Management, 2013)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Recommendation for the discrimination of human-related and natural seismicity - T. Dahm; D. Becker; M. Bischoff; S. Cesca; B. Dost; R. Fritschen; S. Hainzl; C. D. Klose; D. Kühn; S. Lasocki; Th. Meier; M. Ohrnberger; et al. (Journal of Seismology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Estimating ENSO Influence on the Global Mean Sea Level, 1993–2010 - A. Cazenave; O. Henry; S. Munier; T. Delcroix; A. L. Gordon; B. Meyssignac; W. Llovel; H. Palanisamy; M. Becker (Marine Geodesy, 2012)

An Assessment of Two-Dimensional Past Sea Level Reconstructions Over 1950–2009 Based on Tide-Gauge Data and Different Input Sea Level Grids - B. Meyssignac; M. Becker; W. Llovel; A. Cazenave (Surveys in Geophysics, 2012)

Ubiquitous urease affects soybean susceptibility to fungi - Beatriz Wiebke-Strohm; Giancarlo Pasquali; Márcia Margis-Pinheiro; Marta Bencke; Lauro Bücker-Neto; Arlete B. Becker-Ritt; Anne H. S. Martinelli; Ciliana Rechenmacher; Joseph C. Polacco; Renata Stolf; Francismar C. Marcelino; Ricardo V. Abdelnoor; et al. (Plant Molecular Biology, 2012)

Boric acid as reference substance: pros, cons and standardization - M. J. B. Amorim; T. Natal-da-Luz; J. P. Sousa; S. Loureiro; L. Becker; J. Römbke; A. M. V. M. Soares (Ecotoxicology, 2012)

ENSURF: multi-model sea level forecast – implementation and validation results for the IBIROOS and Western Mediterranean regions - B. Pérez; R. Brouwer; J. Beckers; D. Paradis; C. Balseiro; K. Lyons; M. Cure; M. G. Sotillo; B. Hackett; M. Verlaan; E. A. Fanjul (Ocean Science, 2012)
ENSURF (Ensemble SURge Forecast) is a multi-model application for sea level forecast that makes use of several storm surge or circulation models and near-real time tide gauge data in the region, with the following main goals: 1. providing easy access to existing forecasts, as well as to its performance and model validation, by means of an adequate visualization tool; 2. generation of better forecasts of sea level, including confidence intervals, by means of the Bayesian Model Average technique (BMA). The Bayesian Model Average technique generates an overall forecast probability density function (PDF) by making a weighted average of the individual forecasts PDF's; the weights represent the Bayesian likelihood that a model will give the correct forecast and are continuously updated based on the performance of the models during a recent training period. This implies the technique needs the availability of sea level data from tide gauges in near-real time. The system was implemented for the European Atlantic facade (IBIROOS region) and Western Mediterranean coast based on the MATROOS visualization tool developed by Deltares. Results of validation of the different models and BMA implementation for the main harbours are presented for these regions where this kind of activity is performed for the first time. The system is currently operational at Puertos del Estado and has proved to be useful in the detection of calibration problems in some of the circulation models, in the identification of the systematic differences between baroclinic and barotropic models for sea level forecasts and to demonstrate the feasibility of providing an overall probabilistic forecast, based on the BMA method.

Role of gonadal hormones on mu-opioid-stimulated [35S]GTPγS binding and morphine-mediated antinociception in male and female Sprague–Dawley rats - Elizabeth M. Peckham; Steven M. Graves; Emily Jutkiewicz; Jill B. Becker; John R. Traynor (Psychopharmacology, 2011)

APPLICATION OF SOBEK HYDRAULIC SURFACE WATER MODELS IN THE NETHERLANDS HYDROLOGICAL MODELLING INSTRUMENT - G. F. Prinsen; B. P. J. Becker (Irrigation and Drainage, 2011)
The Netherlands is a low‐lying country in the delta of the Rhine and Meuse rivers. Water management is a challenging task at times of high river discharges, but also during droughts, with salt intrusion being an important issue. When river discharges are low, several inlets in the western parts of the country cannot be used, because salinities exceed the standards. Climate change will increase the frequency of these problems. The Freshwater Policy study within the Dutch Delta Programme investigates how to deal with future freshwater supply and demand in the Netherlands. The Netherlands Hydrological modelling Instrument (NHI) has been developed in recent years by Deltares and Alterra in close cooperation with the Dutch Rijkswaterstaat‐Waterdienst, the Netherlands Environmental Assessment Agency, water boards and consultants. NHI is a set of integrated models for surface water, the unsaturated zone and groundwater. Surface water and salt balances are obtained using a 0‐dimensional water balance approach in combination with results of 1D‐hydrodynamic SOBEK flow models. NHI is the central model used in the Dutch Delta Programme's Freshwater Policy study. We will introduce the principles of NHI, the surface water components and their interaction, and discuss the first results of the study. Copyright © 2011 John Wiley & Sons, Ltd.

Platelet decline as a predictor of brain injury in HIV infection - Ann B. Ragin; Gypsyamber D’Souza; Sandra Reynolds; Eric Miller; Ned Sacktor; Ola A. Selnes; Eileen Martin; Barbara R. Visscher; James T. Becker (Journal of NeuroVirology, 2011)

Resistance trends and in vitro activity of tigecycline and 17 other antimicrobial agents against Gram-positive and Gram-negative organisms, including multidrug-resistant pathogens, in Germany - M. Kresken; K. Becker; H. Seifert; E. Leitner; B. Körber-Irrgang; C. Eiff; P.-A. Löschmann (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Candidate Screening of the TRPC3 Gene in Cerebellar Ataxia - Esther B. E. Becker; Brent L. Fogel; Sanjeev Rajakulendran; Anna Dulneva; Michael G. Hanna; Susan L. Perlman; Daniel H. Geschwind; Kay E. Davies (The Cerebellum, 2011)

Subcortical brain atrophy persists even in HAART-regulated HIV disease - James T. Becker; Joanne Sanders; Sarah K. Madsen; Ann Ragin; Lawrence Kingsley; Victoria Maruca; Bruce Cohen; Karl Goodkin; Eileen Martin; Eric N. Miller; Ned Sacktor; Jeffery R. Alger; et al. (Brain Imaging and Behavior, 2011)

Pulmonary Gene Silencing in Transgenic EGFP Mice Using Aerosolised Chitosan/siRNA Nanoparticles - Ebbe J. B. Nielsen; Jan M. Nielsen; Daniel Becker; Alexander Karlas; Hridayesh Prakash; Sys Z. Glud; Jonathan Merrison; Flemming Besenbacher; Thomas F. Meyer; Jørgen Kjems; Kenneth A. Howard (Pharmaceutical Research, 2010)

Proposal for a revised taxonomy of the family Filoviridae: classification, names of taxa and viruses, and virus abbreviations - Jens H. Kuhn; Stephan Becker; Hideki Ebihara; Thomas W. Geisbert; Karl M. Johnson; Yoshihiro Kawaoka; W. Ian Lipkin; Ana I. Negredo; Sergey V. Netesov; Stuart T. Nichol; Gustavo Palacios; Clarence J. Peters; et al. (Archives of Virology, 2010)

Land-use planning for natural hazards in New Zealand: the setting, barriers, ‘burning issues’ and priority actions - B. C. Glavovic; W. S. A. Saunders; J. S. Becker (Natural Hazards, 2010)

Super-ensemble techniques applied to wave forecast: performance and limitations - F. Lenartz; J.-M. Beckers; J. Chiggiato; B. Mourre; C. Troupin; L. Vandenbulcke; M. Rixen (Ocean Science, 2010)
Nowadays, several operational ocean wave forecasts are available for a same region. These predictions may considerably differ, and to choose the best one is generally a difficult task. The super-ensemble approach, which consists in merging different forecasts and past observations into a single multi-model prediction system, is evaluated in this study. During the DART06 campaigns organized by the NATO Undersea Research Centre, four wave forecasting systems were simultaneously run in the Adriatic Sea, and significant wave height was measured at six stations as well as along the tracks of two remote sensors. This effort provided the necessary data set to compare the skills of various multi-model combination techniques. Our results indicate that a super-ensemble based on the Kalman Filter improves the forecast skills: The bias during both the hindcast and forecast periods is reduced, and the correlation coefficient is similar to that of the best individual model. The spatial extrapolation of local results is not straightforward and requires further investigation to be properly implemented.

Introduction to the Topical Volume: Recent Advances in Nuclear Explosion Monitoring - Andreas Becker; Bernd Schurr; Martin B. Kalinowski; Karl Koch; David Brown (Pure and Applied Geophysics, 2010)

Environmental Radioxenon Levels in Europe: a Comprehensive Overview - Paul R. J. Saey; Clemens Schlosser; Pascal Achim; Matthias Auer; Anders Axelsson; Andreas Becker; Xavier Blanchard; Guy Brachet; Luis Cella; Lars-Erik De Geer; Martin B. Kalinowski; Gilbert Le Petit; et al. (Pure and Applied Geophysics, 2010)

Habitat Split as a Cause of Local Population Declines of Amphibians with Aquatic Larvae - C. GUILHERME BECKER; CARLOS R. FONSECA; CÉLIO F. B. HADDAD; PAULO I. PRADO (Conservation Biology, 2010)
Most amphibian species have biphasic life histories and undergo an ontogenetic shift from aquatic to terrestrial habitats. In deforested landscapes, streams and forest fragments are frequently disjunct, jeopardizing the life cycle of forest‐associated amphibians with aquatic larvae. We tested the impact of habitat split—defined as human‐induced disconnection between habitats used by different life‐history stages of a species—on four forest‐associated amphibian species in a severely fragmented landscape of the Brazilian Atlantic Forest. We surveyed amphibians in forest fragments with and without streams (referred to as wet and dry fragments, respectively), including the adjacent grass‐field matrix. Our comparison of capture rates in dry fragments and nearby streams in the matrix allowed us to evaluate the number of individuals that engaged in high‐risk migrations through nonforested habitats. Adult amphibians moved from dry fragments to matrix streams at the beginning of the rainy season, reproduced, and returned at the end of the breeding period. Juveniles of the year moved to dry fragments along with adults. These risky reproductive migrations through nonforested habitats that expose individuals to dehydration, predation, and other hazards may cause population declines in dry fragments. Indeed, capture rates were significantly lower in dry fragments compared with wet fragments. Declining amphibians would strongly benefit from investments in the conservation and restoration of riparian vegetation and corridors linking breeding and nonbreeding areas.

Global Bathymetry and Elevation Data at 30 Arc Seconds Resolution: SRTM30_PLUS - J. J. Becker; D. T. Sandwell; W. H. F. Smith; J. Braud; B. Binder; J. Depner; D. Fabre; J. Factor; S. Ingalls; S-H. Kim; R. Ladner; K. Marks; et al. (Marine Geodesy, 2009)

Cadmium-induced oxidative stress in two potato cultivars - J. F. Gonçalves; L. A. Tabaldi; D. Cargnelutti; L. B. Pereira; J. Maldaner; A. G. Becker; L. V. Rossato; R. Rauber; M. D. Bagatini; D. A. Bisognin; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2009)

Photosynthetic pigments content, δ-aminolevulinic acid dehydratase and acid phosphatase activities and mineral nutrients concentration in cadmium-exposed Cucumis sativus L. - Jamile F. Gonçalves; Fernando T. Nicoloso; Alexssandro G. Becker; Luciane B. Pereira; Luciane A. Tabaldi; Denise Cargnelutti; Carla M. G. de Pelegrin; Valderi L. Dressler; João B. T. da Rocha; Maria Rosa C. Schetinger (Biologia, 2009)

Repeated cycles of chronic intermittent ethanol exposure in mice increases voluntary ethanol drinking and ethanol concentrations in the nucleus accumbens - William C. Griffin; Marcelo F. Lopez; Amy B. Yanke; Lawrence D. Middaugh; Howard C. Becker (Psychopharmacology, 2009)

Eye–head coordination in moderately affected Huntington’s Disease patients: do head movements facilitate gaze shifts? - W. Becker; R. Jürgens; J. Kassubek; D. Ecker; B. Kramer; B. Landwehrmeyer (Experimental Brain Research, 2009)

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Low‐cost aerial photography for high‐resolution mapping of hydrothermal areas in Yellowstone National Park - B. Planer‐Friedrich; J. Becker; B. Brimer; B. J. Merkel (International Journal of Remote Sensing, 2008)

Modellierung der Randüberströme zwischen Erftscholle, Rurscholle und Venloer Scholle durch Kopplung von Großraum-Grundwassermodellen - B. Becker; J. Köngeter; W. S. Klauder; C. Reuter (Grundwasser, 2008)

Presence of Fish on the Shallow Flooded Margins of a Small Intermittently Open Estuary in South Eastern Australia under Variable Flooding Regimes - Alistair Becker; Laurie J. B. Laurenson (Estuaries and Coasts, 2008)

Is the incidence of perimyocarditis increased following Campylobacter jejuni infection? - S. Becker; T. Ejlertsen; B. Kristensen; M. Nørgaard; H. Nielsen (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Carcinoembryonic antigen-stimulated THP-1 macrophages activate endothelial cells and increase cell–cell adhesion of colorectal cancer cells - Cary B. Aarons; Olga Bajenova; Charles Andrews; Stanley Heydrick; Kristen N. Bushell; Karen L. Reed; Peter Thomas; James M. Becker; Arthur F. Stucchi (Clinical & Experimental Metastasis, 2007)

Das Großraum-Grundwassermodell Rurscholle - D. Bachmann; B. Becker; A. van Linn; J. Köngeter (Grundwasser, 2007)

Kinder-Umwelt-Survey, Pilotstudie (2001/2002): Hinweise auf Expositionspfade für die innere Belastung mit Organophosphaten und Pyrethroiden - K. Becker; M. Seiwert; J. Angerer; M. Kolossa-Gehring; H. -W. Hoppe; C. Schulz; B. Seifert (Journal of Consumer Protection and Food Safety, 2007)

Ion Levels in the Gastrointestinal Tract Content and Plasma of Four Teleosts with Different Feeding Habits - A.G. Becker; J.F. Gonçalves; L.O. Garcia; E.R. Behr; F.J.K. Mallmann; D.L. Graça; B. Baldisserotto (Fish Physiology and Biochemistry, 2006)

Ion levels in the gastrointestinal tract content and plasma of four teleosts with different feeding habits - A.G. Becker; J.F. Gonçalves; L.O. Garcia; E.R. Behr; F.J.K. Mallmann; D.L. Graça; B. Baldisserotto (Fish Physiology and Biochemistry, 2006)

Absolute calibration of GPS antennas: laboratory results and comparison with field and robot techniques - B. Görres; J. Campbell; M. Becker; M. Siemes (GPS Solutions, 2006)

Development and Characterization of a Scalable Controlled Precipitation Process to Enhance the Dissolution of Poorly Water-Soluble Drugs - True L. Rogers; Ian B. Gillespie; James E. Hitt; Kevin L. Fransen; Cindy A. Crowl; Christopher J. Tucker; Gary B. Kupperblatt; Joe N. Becker; Deb L. Wilson; Clifford Todd; Charles F. Broomall; Jonathan C. Evans; et al. (Pharmaceutical Research, 2004)

Wide-range transcriptional modulating effect of ntrR under microaerobiosis in Sinorhizobium meliloti - L. G. Puskás; Z. B. Nagy; J. Z. Kelemen; S. Rüberg; M. Bodogai; A. Becker; I. Dusha (Molecular Genetics and Genomics, 2004)

The genome of Desulfotalea psychrophila , a sulfate‐reducing bacterium from permanently cold Arctic sediments - R. Rabus; A. Ruepp; T. Frickey; T. Rattei; B. Fartmann; M. Stark; M. Bauer; A. Zibat; T. Lombardot; I. Becker; J. Amann; K. Gellner; et al. (Environmental Microbiology, 2004)
Summary Desulfotalea psychrophila is a marine sulfate‐reducing δ‐proteobacterium that is able to grow at in situ temperatures below 0°C. As abundant members of the microbial community in permanently cold marine sediments, D. psychrophila ‐like bacteria contribute to the global cycles of carbon and sulfur. Here, we describe the genome sequence of D. psychrophila strain LSv54, which consists of a 3 523 383 bp circular chromosome with 3118 predicted genes and two plasmids of 121 586 bp and 14 663 bp. Analysis of the genome gave insight into the metabolic properties of the organism, e.g. the presence of TRAP‐T systems as a major route for the uptake of C 4 ‐dicarboxylates, the unexpected presence of genes from the TCA cycle, a TAT secretion system, the lack of a β‐oxidation complex and typical Desulfovibrio cytochromes, such as c 553 , c 3 and ncc. D. psychrophila encodes more than 30 two‐component regulatory systems, including a new Ntr subcluster of hybrid kinases, nine putative cold shock proteins and nine potentially cold shock‐inducible proteins. A comparison of D. psychrophila 's genome features with those of the only other published genome from a sulfate reducer, the hyperthermophilic archaeon Archaeoglobus fulgidus , revealed many striking differences, but only a few shared features.

Survey of Gastric Lesions and Blood Pepsinogen Levels in Pigs in Burkina Faso - H. Banga-Mboko; H. Tamboura; D. Maes; H. Traoré; I. Youssao; P.T. Sangild; B. El Amiri; B. Bayala; B. Remy; J.F. Beckers (Veterinary Research Communications, 2003)

Parasympathetic heart rate modulation during parabolic flights - F. Beckers; B. Seps; D. Ramaekers; B. Verheyden; A. E. Aubert (European Journal of Applied Physiology, 2003)

Erratum - Daniel J. Becker; Jay T. Myers; Melissa M. Ruff; Peter L. Smith; Brenda W. Gillespie; David W. Ginsburg; John B. Lowe (Mammalian Genome, 2003)

Elemental Composition of Liver and Kidney Tissues of Rough-Toothed Dolphins ( Steno bredanensis ) - E. A. Mackey; R. D. Oflaz; M. S. Epstein; B. Buehler; B. J. Porter; T. Rowles; S. A. Wise; P. R. Becker (Archives of Environmental Contamination and Toxicology, 2003)

Strain-specific modification of lethality in fucose-deficient mice - Daniel J. Becker; Jay T. Myers; Melissa M. Ruff; Peter L. Smith; Brenda W. Gillespie; David W. Ginsburg; John B. Lowe (Mammalian Genome, 2003)

Forecasting the Oral Absorption Behavior of Poorly Soluble Weak Bases Using Solubility and Dissolution Studies in Biorelevant Media - Edmund S. Kostewicz; Ulrich Brauns; Robert Becker; Jennifer B. Dressman (Pharmaceutical Research, 2002)

Use of deuterated water as a conservative artificial groundwater tracer - Matthew W. Becker; Tyler B. Coplen (Hydrogeology Journal, 2001)

AFM observations and simulations of jarosite growth at the molecular scale: probing the basis for the incorporation of foreign ions into jarosite as a storage mineral - U. Becker; B. Gasharova (Physics and Chemistry of Minerals, 2001)

Dry miombo – ecology of its major plant species and their potential use as bio-indicators - W. Kanschik; B. Becker (Plant Ecology, 2001)

Intron-mediated enhancement of the banana bunchy top virus DNA-6 promoter in banana (Musa spp.) embryogenic cells and plants - B. Dugdale; D.K. Becker; R.M. Harding; J. L. Dale (Plant Cell Reports, 2001)

Abstracts of Presentations at the 21st congress of the Israeli phytopathological society February 14–15, 2000 ARO, the Volcani Center, Bet Dagan, Israel - S. Droby; G. Kritzman; A. Gamliel; Miriam Austerweil; Yael Skutelski; I. Peretz-Alon; E. Becker; J. Katan; R. Cohen; M. Edelstein; Carmela Horev; Y. Burger; et al. (Phytoparasitica, 2000)

Promoters derived from banana bunchy top virus DNA-1 to −5 direct vascular-associated expression in transgenic banana ( Musa spp.) - B. Dugdale; D. K. Becker; P. R. Beetham; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Linkage mapping and QTL analysis in coconut (Cocos nucifera L.) - A. Herrán; L. Estioko; D. Becker; M. J. B. Rodriguez; W. Rohde; E. Ritter (Theoretical and Applied Genetics, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

The families of papain- and legumain-like cysteine proteinases from embryonic axes and cotyledons of Vicia seeds: developmental patterns, intracellular localization and functions in globulin proteolysis - J. Fischer; C. Becker; S. Hillmer; C. Horstmann; B. Neubohn; A. Schlereth; V. Senyuk; A. Shutov; K. Müntz (Plant Molecular Biology, 2000)

Genetic transformation of Cavendish banana ( Musa spp. AAA group) cv 'Grand Nain' via microprojectile bombardment - D. K. Becker; B. Dugdale; M. K. Smith; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Selectins and β2-integrins mediate post-ischaemic venular adhesion of polymorphonuclear leukocytes, but not capillary plugging, in isolated hearts - H. Habazettl; C. Kupatt; S. Zahler; B. F. Becker; K. Messmer (Pflügers Archiv - European Journal of Physiology, 1999)

Gq/11-coupled receptors and protein synthesis in rat cardiomyocytes: role of Gi-proteins and protein kinase C-isozymes - K. Pönicke; I. Heinroth-Hoffmann; K. Becker; B. Osten; O.-E. Brodde (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Selectins and β 2 -integrins mediate post-ischaemic venular adhesion of polymorphonuclear leukocytes, but not capillary plugging, in isolated hearts - H. Habazettl; C. Kupatt; S. Zahler; B. F. Becker; K. Messmer (Pflügers Archiv - European Journal of Physiology, 1999)

Alterations of the dopaminergic and glutamatergic neurotransmission in adult rats with postnatal ibotenic acid hippocampal lesion - H. Schroeder; G. Grecksch; A. Becker; B. Bogerts; V. Hoellt (Psychopharmacology, 1999)

USING TREND INDICES FOR ENDANGERED SPECIES - L. L. Eberhardt; R. A. Garrott; B. L. Becker (Marine Mammal Science, 1999)
A bstract Initial appraisals of the status of endangered large‐mammal populations may have to depend on indices of population trend. Such indices may possibly be improved by using auxiliary variables. Various models were studied for populations of the Florida manatee ( Trichechus manatus latirostris ), Yellowstone grizzly bear ( Ursus arctos horribilis ), and Hawaiian monk seal ( Monachus schauinslandi ). Several criteria for checking validity of the fitted models were considered, and the simple R 2 criterion appears to provide useful comparisons. Multiple regression models overestimated the rate of change of the East Coast manatee population as determined from three other sources (a covariance model, a non‐linear model, and the rate estimated from reproductive and survival data). A multiple regression model for grizzly bears using three auxiliary variables exhibited a fairly high R 2 (0.84) and appeared to provide a better fit than did a non‐linear model. A beach count index for Hawaiian monk seals seemed to be unreliable for year‐to‐year comparisons in contrast to total population counts and estimates from a capture‐recapture method. The use of auxiliary variables for checking and improving trend index data appears feasible and well worthwhile.

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

CCG repeats in cDNAs from human brain - John J. Kleiderlein; Paul E. Nisson; Joel Jessee; W.-B. Li; K. G. Becker; Michael L. Derby; Christopher A. Ross; R. L. Margolis (Human Genetics, 1998)

Geostatistical Analysis of Surface Sediments in an Acidic Mining Lake - O. Büttner; A. Becker; S. Kellner; B. Kuehn; K. Wendt-Potthoff; D.W. Zachmann; K. Friese (Water, Air, & Soil Pollution, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Molecular characterization and delineation of subtle deletions in de novo “balanced” chromosomal rearrangements - Arun Kumar; Laurie A. Becker; Theresa W. Depinet; J. Marie Haren; C. Lisa Kurtz; Nathaniel H. Robin; Suzanne B. Cassidy; Daynna J. Wolff; S. Schwartz (Human Genetics, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

The effect of fumonisin B1 on the growth of bacteria - B. Becker; H. Bresch; U. Schillinger; P.G. Thiel (World Journal of Microbiology and Biotechnology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Retention of leucocytes in reperfused, isolated hearts does not cause haemodynamically relevant permanent capillary plugging - S. Zahler; C. Kupatt; C. Seligmann; C. Kowalski; B. F. Becker; E. Gerlach (Pflügers Archiv - European Journal of Physiology, 1997)

Bioaccumulation of vanadium and other trace metals in livers of Alaskan cetaceans and pinnipeds - E. A. Mackey; P. R. Becker; R. Demiralp; R. R. Greenberg; B. J. Koster; S. A. Wise (Archives of Environmental Contamination and Toxicology, 1996)

Bioaccumulation of Vanadium and Other Trace Metals in Livers of Alaskan Cetaceans and Pinnipeds - E. A. Mackey; P. R. Becker, R. Demiralp; R. R. Greenberg; B. J. Koster; S. A. Wise (Archives of Environmental Contamination and Toxicology, 1996)

Analysis, classification, and coding of multielectrode spike trains with hidden Markov models - G. Radons; J. D. Becker; B. Dülfer; J. Krüger (Biological Cybernetics, 1994)

Analysis, classification, and coding of multielectrode spike trains with hidden Markov models - G. Radons; J. D. Becker; B. Dlfer; J. Krger (Biological Cybernetics, 1994)

Lack of direct immunosuppressive effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on human peripheral blood lymphocyte subsets in vitro - Dagmar S. Lang; Susannne Becker; George C. Clark; Robert B. Devlin; Hillel S. Koren (Archives of Toxicology, 1994)

Indigenous knowledge in a ?modern? sustainable agroforestry system?a case study from eastern Brazil - B. Schulz; B. Becker; E. Gtsch (Agroforestry Systems, 1994)

Ultrastructural studies on a chlorella virus from Germany - B. Becker; D. E. Lesemann; W. Reisser (Archives of Virology, 1993)

Microtubular reaction in human fibroblasts infected by cytomegalovirus - G. Pfeiffer; D. Willutzki; D. Weder; B. Becker; K. Radsak (Archives of Virology, 1983)

Herpes simplex virus DNA polymerase, thymidine kinase and deoxyribonuclease activities in cells infected with wild type, ultraviolet-irradiated and defective virus - Y. Becker; B. Gutter; Yaffa Cohen; N. Chejanovsky; S. Rabkin; B. Fridlender (Archives of Virology, 1979)

Effect of pregnancy on hepatic microsomal drug metabolism in rabbits and rats - I. Gut; B. A. Becker; M. Gutov (Archives of Toxicology, 1976)

Heredity of hexobarbital sleeping time and efficiency of drug metabolism in Wistar and Sprague-Dawley rats - I. Gut; B. A. Becker (Archives of Toxicology, 1975)